THE MILITARY, THE 2019 GENERAL ELECTIONS AND THE FUTURE OF DEMOCRACY IN NIGERIA - A. IKENGA, Francis (International Journal of Psychosocial Rehabilitation, 2020)
A major issue that occurred in the general elections of February 2019 was the involvement of military personnel who also acted as security operatives. They were also given direct order to put the state on a lockdown shortly before, during and after the elections, with rapid consequences on the people’s right and freedom. The major targets were the opposition members who did not belong to the ruling party. The pertinent questions to ask then are: What accounts for this? What are its implications on democratic consolidation? Data for the study were collected using the historical method and analyzed using qualitative analysis. This paper is not an exception to other papers which might have dealt extensively on military deployment in the 2019 elections. Other regimes since 1999 have also done the same by deploying military personnel during elections. This paper finds out that the military went against their rules of engagement and allowed selfish politicians to use them. It was also noted that, due to the high rate of insecurity in Nigeria, the constitution makes way for the military to come into action. Based on these findings, it was suggested that the security forces that exist in the country which includes the military and INEC, should work together to provide efficient security for the electorates, election materials and INEC staff during elections.